The usefulness of examining terrorists’ rhetoric for understanding the nature of different terror groups - Honig, Or Arthur (Terrorism and political violence, 2019)
This study advances a distinction between two generic types of terrorists’ rhetoric: (1) ideological rhetoric candidly reflecting the terrorists’ genuine beliefs and values regarding their military targeting policy (who is a legitimate target), even when adopting such rhetoric involves high image/diplomatic costs; and (2) a PR-oriented rhetoric which consciously misrepresents the terrorists’ intentions and behavior in an attempt to project a more benign and humane image, thus maintaining sympathy and rebuffing criticism. We contend that such a distinction can provide a highly useful metric for assessing terrorists groups’ rationality and pragmatism: the most pragmatic groups will shift between these two types of rhetoric depending on changing strategic needs. To show the practical usefulness of this distinction we provide criteria for categorizing terrorists’ rhetorical responses to (mostly liberal-minded) criticism that they have killed innocent civilians in their enemy’s camp. We apply our criteria by examining terrorists’ (sincere and insincere) apologies.